Oxidative dehydrogenation of ethylbenzene over vanadia-alumina catalysts in the presence of nitrous oxide: structure-activity relationship - Shiju, N. R.; Anilkumar, Mettu; Mirajkar, Subhash P.; Gopinath, Chinnakonda S.; Rao, B. S.; Satyanarayana, C. V. (Journal of Catalysis, 2005)
A series of vanadia-alumina catalysts with different vanadia contents were prepared by a wet impregnation method. The influence of the local structure of vanadia in these catalysts on the oxidative dehydrogenation of ethylbenzene with nitrous oxide was investigated. The use of N2O as a co-feed remarkably enhanced the styrene yield compared with the use of N-2. Characterization of these vanadia catalysts by XRD, FTIR, UV-vis, TPR, XPS, and V-51 NMR techniques suggests that the nature of the VOx species depends on the vanadia loading: the predominant species are monomeric vanadia at lower loadings, two-dimensional polyvanadates at intermediate loadings, and bulk-like V2O5 and AlVO4 at higher loadings. The rate of oxidative dehydrogenation (ODH) of ethylbenzene per vanadium atom increases with vanadia loading and reaches a maximum at 10 wt%, the loading at which the surface predominantly contains polyvanadate species. The observed variation in the selectivity of products with vanadium loading indicates that the monomeric V5+ species favors dehydrogenation, whereas bulk-like V2O5 preferentially participates in the dealkylation of ethylbenzene. The vanadium species remains at a higher oxidation state in the presence of N2O, leading to a higher styrene yield. than in a N-2 atmosphere. The ODH turnover rates increased with decreasing energy of the absorption edge in the UV-vis spectrum, at low VOx coverages of less than one monolayer on the Al2O3 surface. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: absorption edge energy; Alumina; ethylbenzene; Nitrous oxide; oxidative dehydrogenation; polyvanadates; styrene; vanadia

Synthesis of bismuth oxide nanoparticles by citrate gel method - Anilkumar, Mettu; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and citric acid solution is taken in 1: 1 molar ratio and heated on hot water bath. A gel is formed on evaporation of the water, which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nanocrystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these powders. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Electron microscopy; powders : chemical preparation; X-ray methods

Synthesis of bismuth titanate by the urea method - Anilkumar, Mettu; Dhage, S. R.; Ravi, V. (Materials Letters, 2005)
A simple urea precipitation route was adopted for the preparation of bismuth titanate (Bi4Ti3O12) powders. Stoichiometric quantities of BiCl3 and TiOCl2 were mixed with the required amount of urea (the ratio of total metal cations to urea is five), and the mixture was heated on a water bath. This leads to the formation of precipitate, which was decomposed at 973 K. The formation of bismuth titanate was observed on calcining powders at 973 K by X-ray diffraction studies. The average particle size is found to be 100 nm by microscopy. The room temperature dielectric constant is found to be 150 at 1 kHz. The hysteresis loop parameters were also obtained by home-built Sawer-Tower circuit. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; dielectric properties; ferroelectricity; X-ray diffraction

Synthesis of nanocrystalline Mn3O4 at 100 degrees C - Anilkumar, Mettu; Ravi, V. (Materials Research Bulletin, 2005)
A simple gel to crystal conversion route has been followed for the preparation of nanocrystalline tetragonal Mn3O4 powders at 80-100 degrees C under refluxing conditions. Freshly prepared manganese hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 4-6 h. Formation of nano crystallites of Mn3O4 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these powders. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Vapour phase oxidation of acetophenone to benzoic acid over binary oxides of V and Mo - Chumbhale, Vilas R.; Paradhy, S. A.; Anilkumar, Mettu; Kadam, S. T.; Bokade, Vijay V. (Chemical Engineering Research and Design, 2005)
Test data for catalytic oxidation of acetophenone into benzoic acid performed at bench scale with V2O5-MoO3 catalyst in a continuous downflow metal reactor are presented. The process parameters such as temperature and flow rate influence the product distribution. The P2O5, B2O3 and Na2O when used as dopant on V2O5-MoO3 catalyst showed marked influence on activity and selectivity. An acidic catalyst like V2O5-MoO3-P2O5 favours formation of benzoic acid while a basic catalyst like V2O5-MoO3-Na2O favours formation of benzaldehyde. The addition of Na2O into V2O5-MoO3 binary oxides formed new phases (NaVMoO6 and Na2V2Mo3O15), which increased Arrhenius activation energy from 18.24 to 31.35 kcal mol(-1).
Keywords: acetophenone; activity; benzoic acid; carbon oxides; oxidation of acetophenone; selectivity

Vapour phase methylation of phenol over nanocrystalline ZnFe(2-x)A1(x)O(4) (x=0, 0.25, 0.5, 0.75 and 1.0) ferrospinel system - Reddy, Vanga S.; RadheShyam, A.; Dwivedi, Reena; Rai, A.; Anilkumar, Mettu; Chumbhale, Vilas R.; Aswar, A. S.; Prasad, R. (Indian Journal of Chemical Technology, 2006)
The alkylation ofphenol with methanol was carried out over ZnFe2-xAlxO4 (x = 0, 0.25, 0.5, 0.75 and 1.0) type spinel systems in a Fixed bed, down flow reactor. The influence of Surface acidity, cation distribution in the spinel lattice and various reaction parameters are discussed. A maximum yield of 70.9 and 22.9% with selectivity of 73.5 and 23.3% was obtained for 2,6-xylenol and o-cresol respectively, giving a total ortho selectivity of: 96.8% over ZnFeAlO4 at 350 degrees C, methanol to phenol molar ratio of 5 and WHSV of 0.6 h(-1). Catalyst characterization was made by XRD, Mossbauer spectroscopy, ammonia desorption and BET surface area measurements. Mossbauer spectroscopy reveals isomorphic substitution or Fe 3 by smaller A 13, into the octahedral sites leading to lattice distortion, Unsymmetrical charge distribution and charge transfer from iron to oxygen making it more basic and proton attracting. This helps vertical adsorption ofphenol and formation of 2.6-xylenol. It has been concluded that catalyst acidity plays major role in the reaction as compared to surface area.
Keywords: consecutive methylation; ferrospinels; vertical and horizontal adsorption

Oxidative dehydrogenation of ethylbenzene using nitrous oxide over vanadia-magnesia catalysts - Shiju, N. Raveendran; Anilkumar, Mettu; Gokhale, S. P.; Rao, B. Seshagiri; Satyanarayana, C. V. V. (Catalysis Science & Technology, 2011)
A series of V-Mg-O catalysts with different loadings of vanadia were prepared by the wet impregnation method and the effect of the local structure of these catalysts on the oxidative dehydrogenation of ethylbenzene with N(2)O was investigated. High styrene selectivity (similar to 97%) was obtained at 773 K. The characterization of catalysts with methods such as XRD, FTIR, UV-visible, TPR, NMR and Laser Raman spectroscopy suggested that magnesium orthovanadate is the predominant vanadium containing phase and the size of the orthovanadate domains increases with increasing vanadia loading. The rate of ODH of ethylbenzene per V atom increases with vanadia loading and reaches a maximum at 10 wt%. The specific activity, i.e. the conversion of ethylbenzene per unit surface area of the catalysts, also exhibited a maximum at a vanadia loading of 10 wt% leading to the conclusion that activity of these catalysts is due to the presence of very small domains of Mg(3)(VO(4))(2) on the surface of MgO rather than crystallites of bulk Mg(3)(VO(4))(2). The higher styrene yield in the presence of N(2)O can be ascribed to the ability of N(2)O to keep vanadium species at a higher oxidation state.